An Islamic psychospiritual-acceptance and commitment-based prevention intervention program for at-risk young adults in Covid-19 pandemic (SPI21-052-0052) - Abdul Khaiyom, Jamilah Hanum; Md Rosli, Ahmad Nabil; Bahari, Che Amnah; Abdullah, Nur Sakinah Thomas; Abdul Aziz, Amani Fadzlina (2022)
Aims of the study: - To develop i-ACT For Life, a web-based Islamic psychospiritual ACT-based prevention program - To investigate the effectiveness of i-ACT for Life, a web-based Islamic psychospiritual ACT-based prevention program in reducing psychological distress and improving the psychological flexibility, self-compassion, and resilience of at-risk young adults in Malaysia during the COVID-19 pandemic.